Negative Perception of the COVID-19 Pandemic Is Dropping: Evidence From Twitter Posts - Vargas, Alessandro N.; Maier, Alexander; Vallim, Marcos B. R.; Banda, Juan M.; Preciado, Victor M. (Frontiers in Psychology, 2021)
The Covid-19 pandemic hit hard society, strongly affecting people's emotions and well-being. It is difficult to measure how the pandemic has affected people's sentiment, not to mention how people responded to the dramatic events that took place during the pandemic. This paper contributes to this discussion by showing that people's negative perception of the Covid-19 pandemic is dropping. By negative perception, we mean the number of negative words the users of Twitter, a social media platform, employ in their online posts. Seen as aggregate, Twitter users are using less and less negative words as the pandemic evolves. The conclusion that the negative perception is dropping comes from a careful analysis we made in the contents of the Covid-19 Twitter chatter dataset, a comprehensive database accounting for more than one billion posts generated during the pandemic. We explore why people's negativity decreases, making connections with psychological traits such as psychophysical numbing, reappraisal, suppression, and resilience. In particular, we show that the negative perception decreased intensively when the vaccination campaign started in the USA, Canada, and the UK and has remained to decrease steadily since then. This finding led us to conclude that vaccination plays a key role in dropping people's negativity, thus promoting their psychological well-being.